2021
DOI: 10.1017/s1357321721000015
|View full text |Cite
|
Sign up to set email alerts
|

The IFRS 17 contractual service margin: a life insurance perspective

Abstract: IFRS 17 Insurance Contracts is a new accounting standard currently expected to come into force on 1 January 2023. It supersedes IFRS 4 Insurance Contracts. IFRS 17 establishes key principles that entities must apply in all aspects of the accounting of insurance contracts. In doing so, the Standard aims to increase the usefulness, comparability, transparency and quality of financial statements. A fundamental concept introduced by IFRS 17 is the contractual service margin (CSM). This represents the unearned p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 0 publications
0
5
0
1
Order By: Relevance
“…If the insurance business continues to accept the onerous contract, the initial contract loss must be recognized and recorded in the income statement (Widing & Jansson, 2018). If the contract is not onerous, the insurance company may consider whether it is part of a profitable "fat" contract (no substantial probability of being onerous) or a deal that is slightly more classified as onerous (Widing & Jansson, 2018;Yousuf et al, 2020). If the contract is lucrative, the insurance company will recognize the unearned CSM as insurance service performed and release it.…”
Section: Figure 7 the "Cohorts" Process Of Psak 74mentioning
confidence: 99%
See 3 more Smart Citations
“…If the insurance business continues to accept the onerous contract, the initial contract loss must be recognized and recorded in the income statement (Widing & Jansson, 2018). If the contract is not onerous, the insurance company may consider whether it is part of a profitable "fat" contract (no substantial probability of being onerous) or a deal that is slightly more classified as onerous (Widing & Jansson, 2018;Yousuf et al, 2020). If the contract is lucrative, the insurance company will recognize the unearned CSM as insurance service performed and release it.…”
Section: Figure 7 the "Cohorts" Process Of Psak 74mentioning
confidence: 99%
“…The PSAK 74 model for measuring the value of insurance schemes is a powerful actuarial tool and yet arduous (Dahiyat & Owais, 2021;Muskitta & Safitri, 2019;Yousuf et al, 2020). In general, there are three measurement models proposed by PSAK 74 to account for the insurance contract, namely the building-block model, variable-fee approach, and premium allocation GPPC, 2020;KPMG, 2020;PWC, 2020).…”
Section: Measurement Of Insurance Policy: Enchanting the Building-blo...mentioning
confidence: 99%
See 2 more Smart Citations
“…The CSM is (Domingues, 2019, p. 20) a component that reflects the unearned profit of a group of contracts. A very detailed description of the CSM is presented in the paper of Yousuf et al (2021), where they have concluded that the determination of coverage units or the calculation of the CSM at transition have a significant impact on the final amount of the CSM. England et al (2019, p. 75) mention the explanation of the risk margin in accordance with Solvency II in the context of risk adjustment according to IFRS 17.…”
Section: Review Of the Literaturementioning
confidence: 99%